Forensic soil analysis using laser-induced breakdown spectroscopy (LIBS) and Fourier transform infrared total attenuated reflectance spectroscopy (FTIR-ATR): Principles and case studies - Xu, Xuebin; Du, Changwen; Ma, Fei; Shen, Yazhen; Zhou, Jianmin (Forensic science international, 2020)
[Display omitted] •Explorations of LIBS and FTIR-ATR techniques in soil forensic identification.•Optimizations of LIBS and FTIR-ATR in soil forensic identification.•Fusions of the LIBS and FTIR-ATR spectra data in soil forensic analysis.•Applications of LIBS and FTIR-ATR in real cases of soil forensics analysis. Soils are crucial trace evidence that can establish or exclude the relationship between a suspect, victim, or an object at a particular scene, which could contribute to building a case. Laser-induced breakdown spectroscopy (LIBS) and Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy have been demonstrated to be effective techniques for soil characterization owing to its being rapid, non-destructive, and convenient analysis with little sample preparation requirements. Therefore, the principles of LIBS and FTIR-ATR techniques for soil forensic analysis in typical soil samples were investigated and their practical feasibility was tested by applying the techniques to forensic soil samples in two criminal cases. Principal component analysis (PCA) of a typical soil sample indicated that five typical soil types were clearly distinguished by LIBS and FTIR-ATR spectra. Variations in the soil elements (i.e., Si, Mg, Al, Ca, K, O, and N) and functional groups (i.e., OH/NH, CC/CO, SiO, CO32−, AlOH, and NH2) are crucial indicators for soil identification. The casework results demonstrated that both LIBS and FTIR-ATR show great potential for forensic soil analysis in future cases.